2018
DOI: 10.1017/jfm.2018.822
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence in intermittent transitional boundary layers and in turbulence spots

Abstract: Direct numerical simulation data of bypass transition in flat-plate boundary layers are analysed to examine the characteristics of turbulence in the transitional regime. When intermittency is 50 % or less, the flow features a juxtaposition of turbulence spots surrounded by streaky laminar regions. Conditionally averaged turbulence statistics are evaluated within the spots, and are compared to standard time averaging in both the transition region and in fully turbulent boundary layers. The turbulent-conditioned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 46 publications
5
34
0
Order By: Relevance
“…In plane Couette flow [28,49], the upstream and downstream spatial decay rates are equal, by virtue of symmetry, while those of pipe flow show a strong dependence of the upstream decay rate on Reynolds number [50]. Asymmetry between upstream and downstream spatial decay rates is also seen in turbulent spots in boundary layer flow [51] and in Poiseuille-Couette flow [52].…”
Section: Band Velocity and Interaction Lengthmentioning
confidence: 95%
“…In plane Couette flow [28,49], the upstream and downstream spatial decay rates are equal, by virtue of symmetry, while those of pipe flow show a strong dependence of the upstream decay rate on Reynolds number [50]. Asymmetry between upstream and downstream spatial decay rates is also seen in turbulent spots in boundary layer flow [51] and in Poiseuille-Couette flow [52].…”
Section: Band Velocity and Interaction Lengthmentioning
confidence: 95%
“…The Reynolds stresses from the current LES are also in a good agreement with the reference data. Since the current LES data is for a compressible boundary layer that has a higher momentum thickness Reynolds number and friction Reynolds number , the velocity profile has a slightly larger plateau value and the streamwise Reynolds stress profile has a higher peak value in the buffer layer (Marxen & Zaki 2019). Note that the grid sensitivity has been checked using two coarser grids with and .…”
Section: Flow Configuration and Numerical Set-upmentioning
confidence: 99%
“…More recently, the concept of edge state, which originates from the dynamics of systems, has been applied in combination with the receptivity of boundary layers to explain the nucleation mechanism for turbulent spots (Khapko et al 2016;Kreilos et al 2016). Based on conditional statistics of the bypass transition in flat-plate boundary layers, Marxen & Zaki (2019) found that turbulent spots can develop a core region with similar statistics to fully turbulent boundary layers, while the edge shows elevated levels of Reynolds stresses.…”
Section: Introductionmentioning
confidence: 99%